Peucetia casseli Simon, 1900 has priority over P. longipes Pocock, 1900 (Araneae, Oxyopidae) - Blick, Theo; Gloor, Daniel (Zootaxa, 2017)
The World Spider Catalog (WSC 2016) currently lists Peucetia longipes Pocock, 1899 as a senior synonym of P. casseli Simon, 1899; according to Niekerk & Dippenaar-Schoeman (1994: 16). The synonymy decision per se is not to be doubted but, regarding the senior name choice, it was stated that “As both P. [Peucetia] longipes and P. casseli were described in 1899, we decided to give P. longipes priority over P. casseli as the former species was more often referred to in the literature.” So Niekerk & Dippenaar-Schoeman (1994) did not check the month or even the day of the two relevant publications.